Stromal immunoglobulin κC expression is associated with initiation of breast cancer in TA2 mice and human breast cancer. Issue 6 (23rd May 2018) - Zhang, Shiwu; Fei, Fei; Wang, Hua; Gu, Yanjun; Li, Chunyuan; Wang, Xinlu; Zhao, Yongjie; Li, Yuwei
Abstract : The initiation of spontaneous breast cancer (SBC) in Tientsin Albino 2 (TA2) mice is related to mouse mammary tumor virus (MMTV) infection, and MMTV amplification is hormonally regulated. To explore the insertion site of MMTVLTR in TA2 mouse genome, reverse PCR and nested PCR were used to amplify the unknown sequence on both sides of the MMTV‐LTRSAG gene in SBC and normal breast tissue of TA2 mice. Furthermore, the clinicopathological significance of the insertion site was evaluated in 43 samples of normal breast tissue, 46 samples of breast cystic hyperplasia, 54 samples of ductal carcinoma in situ, 142 samples of primary breast cancer and 47 samples of lymph node metastatic breast cancer by RNA in situ hybridization. We confirmed that the insertion site of the MMTV‐LTRSAG gene was located between Igκ v2‐112 and Igκ v14‐111 in chromosome 6 of TA2 mouse. IGκ C was localized in the stromal cells of TA2 mouse with SBC and in human breast cancer tissues. Tumor cells were negative for IGκ C in RNA in situ hybridization. The positive staining index of IGκ C in stromal cells was the highest in lymph node metastatic breast cancer, followed by primary breast cancer, ductal carcinoma in situ, and breast cystic hyperplasia. Furthermore, the positive staining index of IGκ C was related to the expression of ER, PR, HER2 and Ki‐67. Our findings showed that stromal IGκ C expression was associated with the initiation of SBC in TA2 mice. IGκ C may be a high‐risk factor for the initiation and progression of human breast cancer. Abstract : Stromal IGκC expression was associated with the initiation of SBC in TA2 mice. IGκC may be a high‐risk factor for the initiation and progression of human breast cancer.